2021
DOI: 10.1111/jfbc.13831
|View full text |Cite
|
Sign up to set email alerts
|

An insight on the nature of biochemical interactions between glycyrrhizin, myricetin and CYP3A4 isoform

Abstract: Drug interaction studies are imperative to gain insights into the beneficial or harmful effects of therapeutic and dietary agents. This study investigated the mechanism of modulatory roles of glycyrrhizin (GLH) and myricetin (MYC) on the human CYP3A4 isoform using in silico and in vitro methods. While MYC had concentration‐dependent inhibitory effect on CYP3A4 (IC50: 10.5 ± 0.55 μM) with characteristic Km and Vmax values of 1.13 μM and 1.54 nM/min, respectively, GLH exhibited no inhibitory effect on CYP3A4 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Using PTRAJ, the systems were subsequently saved, and each trajectory was analyzed every 1 ps, and the RMSD, Radius of Gyration (RoG), Root Mean Square Fluctuation, Solvent Accessible Surface Area (SASA), and the H-bond flexibility were analysed with AMBER 18 suite of CPPTRAJ module. The Molecular Mechanics/GB Surface Area method (MM/GBSA) was used for the analysis of the negative free binding energy (∆G) over 100,000 snapshots extracted from the 100 ns trajectory [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using PTRAJ, the systems were subsequently saved, and each trajectory was analyzed every 1 ps, and the RMSD, Radius of Gyration (RoG), Root Mean Square Fluctuation, Solvent Accessible Surface Area (SASA), and the H-bond flexibility were analysed with AMBER 18 suite of CPPTRAJ module. The Molecular Mechanics/GB Surface Area method (MM/GBSA) was used for the analysis of the negative free binding energy (∆G) over 100,000 snapshots extracted from the 100 ns trajectory [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CYP3A4 is one of the most vital isoenzymes belonging to the P450 family and is responsible for metabolism of several (> 60%) drugs, hence potentiating a crucial biological and medicinal application [ 36 , 37 ]. Studies have revealed a higher risk of adverse effects and negative impact on the efficacy of coadministered drugs under influence of CYP3A4 [ 38 , 39 ]. Thus, assessing the probable interactions between therapeutic agents and CYP3A4 is imperative to their application.…”
Section: Discussionmentioning
confidence: 99%
“…However, the P-glycoprotein e ux system found in the GI tract, blood-brain barrier, and several regions of the body [20,36] could limit the bioavailability of the molecules that were predicted to be P-gp substrates. Except for arjungenin, friedelin, nicotine, and terminalin-A, the compounds found in KWAPF01 could bring about some form of drug-drug interactions when they are administered with other drugs as they all inhibit some signi cant cytochrome isoforms, which are responsible for most cytochrome biotransformation [37,38].…”
Section: Discussionmentioning
confidence: 99%